Berberine Protects Against NLRP3 Inflammasome via Ameliorating Autophagic Impairment in MPTP-Induced Parkinson’s Disease Model - Huang, Shuxuan; Liu, Hanqun; Lin, Yuwan; Liu, Muchang; Li, Yanhua; Mao, Hengxu; Zhang, Zhiling; Zhang, Yunlong; Ye, Panghai; Ding, Liuyan; Zhu, Ziting; Yang, Xinling; et al. (Frontiers in Pharmacology, 2021)
The NLR family pyrin domain containing 3 (NLRP3) inflammasome was reported to be regulated by autophagy and activated during inflammatory procession of Parkinson’s disease (PD). Berberine (BBR) is well-studied to play an important role in promoting anti-inflammatory response to mediate the autophagy activity. However, the effect of BBR on NLRP3 inflammasome in PD and its potential mechanisms remain unclear. Hence, in this study, we investigated the effects of BBR on 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mice, by evaluating their behavioral changes, dopaminergic (DA) neurons loss, neuroinflammation, NLRP3 inflammasome and autophagic activity. BBR was also applied in BV2 cells treated with 1-methyl-4-pehnyl-pyridine (MPP+). The autophagy inhibitor 3-Methyladenine (3-MA) was administrated to block autophagy activity both in vivo and in vitro. In our in vivo studies, compared to MPTP group, mice in MPTP+BBR group showed significant amelioration of behavioral disorders, mitigation of neurotoxicity and NLRP3-associated neuroinflammation, enhancement of the autophagic process in substantia nigra (SN). In vitro, compared to MPP+ group, BBR significantly decreased the level of NLRP3 inflammasome including the expressions of NLRP3, PYD and CARD domain containing (PYCARD), cleaved caspase 1 (CASP1), and mature interleukin 1 beta (IL1B), via enhancing autophagic activity. Furthermore, BBR treatment increased the formation of autophagosomes in MPP+-treated BV2 cells. Taken together, our data indicated that BBR prevents NLRP3 inflammasome activation and restores autophagic activity to protect DA neurons against degeneration in vivo and in vitro, suggesting that BBR may be a potential therapeutic to treat PD.